Teachers' Understanding and Implementation of the Merdeka Curriculum in Indonesian Elementary Schools - Yuni Rahmawati; Herlina Herlina; Sisriawan Lapasere; Yusdin Bin M Gagaramusu; Mas'adi Mas'adi; Surahman Surahman (Papanda Publisher, 2026)
Teachers' comprehensive understanding of the Independent Curriculum constitutes a fundamental prerequisite for successful educational transformation in Indonesia. Despite nationwide policy implementation through Permendikbudristek No. 12 of 2024, limited empirical evidence exists regarding teachers' depth of curriculum comprehension at the elementary level. This qualitative descriptive study, grounded in postpositivist paradigm, examined four classroom teachers at SD BK Jonooge through semi-structured interviews, systematic classroom observations, and document analysis. Data were analyzed using Miles and Huberman's interactive model, encompassing data reduction, display, and conclusion drawing. Findings revealed that curriculum implementation remains suboptimal, with teachers demonstrating limited understanding of core components including learning outcomes (CP), learning goal flows (ATP), and project-based learning principles. Implementation challenges manifested in persistent traditional pedagogical approaches, symbolic integration of Pancasila Student Profile values, and predominant summative assessment practices. These deficits stemmed primarily from severely inadequate professional development—training conducted only once biennially—compounded by insufficient facilities and limited professional learning community participation. Paradoxically, student learning outcomes showed improvement despite incomplete implementation fidelity. The study elaborates teacher understanding as a multidimensional construct encompassing cognitive, pedagogical, and metacognitive dimensions, challenging deficit-oriented implementation narratives. Findings underscore urgent need for sustained, job-embedded professional development utilizing collaborative learning models, establishment of robust professional learning communities, and redesigned curriculum materials with explicit implementation guidance to optimize educational transformation.